A retrospective study evaluating the patterns of primary glomerular disease at Charlotte Maxeke Johannesburg academic hospital - Patchapen, Yvette (My University, 2017)
Background Glomerular disease is a frequent and important cause of renal dysfunction. Current data on the patterns of glomerular disease in South Africa is lacking. The aim of this study was to characterize the prevalence and nature of presentation of primary glomerular disease at Charlotte Maxeke Johannesburg Academic Hospital. Materials And Methods This single center, retrospective observational study was performed on adult native renal biopsies over a 10 year period from 2001 - 2010. A total of 1495 native renal biopsies were reviewed. After exclusion of common secondary causes, the results of 194 patients with primary glomerular disease were evaluated. Results The most frequent primary glomerular disease was FSGS (29.8%) followed by MN (19.5%), MPGN (18%), MCD (17%) and IgAN (3%). Nephrotic range proteinuria (60.5%) and unexplained renal dysfunction (24.2%) were the most common indications for biopsy. There was a 59.4% male predominance. From the 73.9 % of patients of African descent, 34.1% presented with FSGS. The majority of patients (62.9%) were aged between 18-49 years with 30.3% of them presenting with FSGS. FSGS presented with a median creatinine 183.5 [101 - 476] mmol/l and mean UPCR (0.89 ± 0.66) g/mmol. There were no statistically significant differences in albumin, haemoglobin and triglycerides between the glomerular disease subtypes. The highest urine leucocytes and dysmorphic red cells were from the IgAN subtype. Most patients, 56.8% had no casts observed, and 39.1% were hypertensive. No change in the pattern of glomerular injury was observed over the course of the study. Conclusion Glomerular pathology is more common in younger patients. FSGS is more common than other glomerular pathologies in our setting; which may partly be due to local biopsy practices and patient demographics. Clinical parameters do not adequately predict biopsy findings.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Masters in Medicine (Internal Medicine) Johannesburg 2017
Keywords: Primary Glomerular; Primary Glomerular